A triangular double layer microchannel heat sink: effect of parallel and counter flow - Manaf, Hazli; Ahmed, Shugata; Ahmed, Mirghani Ishak; Hawlader, Mohammad Nurul Alam (2014)
A numerical study is conducted by using ANSYS CFX 14.5, a commercial computational fluid dynamics program to predict the thermal performance of a counter and parallel flow on triangular double layered micro-channel heat sink for various channel aspect ratios. Findings reveal that the counter flow configuration leads to a better heat transfer performance for low channel aspect ratio (α < 4) and higher Reynolds Number (Re > 700). For the parallel flow configuration, improved performance is normally shown when channel aspect ratio, α is more than 4 and lower Reynolds Number (Re < 700).